![\frac{1}{2}(x+5)^2 + 9 = -15](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%28x%2B5%29%5E2%20%2B%209%20%3D%20-15%20)
![\frac{(x+5)^2+18}{2} = \frac{-30}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28x%2B5%29%5E2%2B18%7D%7B2%7D%20%3D%20%20%5Cfrac%7B-30%7D%7B2%7D%20)
Cancel out the denominators.
(x+5)² + 18 = -30
(x+5)² = -30 - 18
(x+5)² = -48
The equation is impossible, we have a negative number.
There isn't a number that squared gives a negative number (the square is always positive).
√(x+5)² = +/- √-48
x+5 = +/- √-48
IMPOSSIBLE
You can write the result in imaginary numbers
x+5=+/- 4i√3
Answer:
The plans will cost the same when the amount you have to pay for talking for "x" minutes on Plan A is the same has what you have to pay for talking for the same number of "x" minutes when using Plan B.
$$ Plan A = $$ Plan B
To find the charge on each plan we add the base rate to the per minute call rate for each.
Plan A = $27 + $0.11x
Plan B = $13 + $0.15x
Let's drop the $ sign for now and get rid of the decimal point by multiplying by 100.
2700 + 11x = 1300 + 15x
Subtracting 11x and 1300 from both sides:
4x = 1400
x = 350 min.
Using this result the plans both cost $65.50 for 350 min of talk time.
Step-by-step explanation:
boom :)
Answer:
77.76 times
Step-by-step explanation:
The average distance of Neptune from the sun
= 4.503 × 10
⁹ k
m
.
and Mercury = 5.791 × 10
⁷ k
m
.
Hence neptune is ( 4.503 × 10
⁹) ÷ (5.791
×
10
⁷ ) times farther from the sun than mercury
i.e.(
) × 10⁹⁻⁷ times
=
0.7776 × 10
² times
=
77.76 times.
Answer:
Step-by-step explanation:
5c+1+3c=61
8c+1=61
8c=62
c=7.75
Let's solve your equation step-by-step.<span><span><span>4.5<span>(8−x)</span></span>+36</span>=<span>102−<span>2.5<span>(<span>3x+24</span>)</span></span></span></span>Step 1: Simplify both sides of the equation.<span><span><span>4.5<span>(8−x)</span></span>+36</span>=<span>102−<span>2.5<span>(<span>3x+24</span>)</span></span></span></span>Simplify: (Show steps)<span><span><span>−4.5x</span>+72</span>=<span><span>−7.5x</span>+42</span></span>Step 2: Add 7.5x to both sides.<span><span><span><span>−4.5x</span>+72</span>+7.5x</span>=<span><span><span>−7.5x</span>+42</span>+7.5x</span></span><span><span>3x+72</span>=42</span>Step 3: Subtract 72 from both sides.<span><span><span>3x+72</span>−72</span>=42−72</span><span>3x=−30</span>Step 4: Divide both sides by 3.<span><span>3x3</span>=<span>−303</span></span><span>x=<span>−<span>10</span></span></span>